2019
DOI: 10.1158/1538-7445.sabcs18-p4-08-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P4-08-06: Impact of molecular subtypes on long-term outcomes in triple-negative breast cancer (TNBC) patients treated with adjuvant AC chemotherapy on SWOG S9313

Abstract: Introduction: TNBC is heterogeneous disease with several molecularly defined subtypes (Lehman et al), each of which may be predictive of response to chemotherapy. TNBC molecular subtypes are associated with varied pathological responses to neoadjuvant chemotherapy. However, subtype specific long-term outcomes for TNBC patients treated with uniform adjuvant chemotherapy are not known. Aims: To characterize long-term outcomes of TNBC molecular subtypes (TNBCtypes) in patients treated with adjuvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Inherent bias toward the selection of generally healthy patients who present for treatment to a cancer centre likely resulted in longer mos, albeit the very small sample size that represented a limitation in that retrospective study. A different distribution of molecular tnbc subtypes in the various studies (something that was not assessed in our study) might also contribute to differences in reported clinical outcomes 45 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Inherent bias toward the selection of generally healthy patients who present for treatment to a cancer centre likely resulted in longer mos, albeit the very small sample size that represented a limitation in that retrospective study. A different distribution of molecular tnbc subtypes in the various studies (something that was not assessed in our study) might also contribute to differences in reported clinical outcomes 45 .…”
Section: Discussionmentioning
confidence: 84%
“…In addition, mos could be calculated only for women with stage iv disease and those for whom relapse or recurrence could not be assessed. Given the variation in the natural history of bca, it would be of great interest to examine, at a future date, early and late recurrence by disease subtype in Canadian women 24,[44][45][46] .…”
Section: Discussionmentioning
confidence: 99%